Cellulolytic activity of wild type and mutant Trichoderma pseudokoningii - Nadalini, Margarete F. de Costa [UNESP]; Pizzirani-Kleiner, Aline A. [UNESP]; Carmona, Eleonora Cano [UNESP] (Wiley, 1999)
Strains of Trichoderma pseudokoningii are promising objects for genetic studies and cellulase production. Auxotrophic mutants with deficiencies in the biosynthesis of aminoacids, nucleotides and vitamins (up to five markers) in addition to morphological aspects like conidial colour were obtained from two strains of double auxotrophic mutants using UV radiation. In order to compare the cellulolytic capabilities of the T. pseudokoningii (wild type strain), some of its mutants and T. reesei QM9414 we performed semiquantitative cellulase assays and quantitative determination of the enzymes exoglucanase and endoglucanase. The semiquantitative test showed that the strains with minimal mycelial growth rate were better producers. Both tests revealed that two of the studied mutants, TG3 and TG4 presented a yield higher than the wild type, reaching 30% more exoglucanase and 70% more endoglucanase. These results indicate that the wild type was improved for cellulase production. Highly significant values of correlation were found for exoglucanase and endoglucanase activities, suggesting that these enzymes may be co-regulated in T. pseudokoningii.
Keywords: amino acid synthesis; cellulase; enzyme activity; enzyme assay; enzymic hydrolysis; exoglucanase; fungal growth; fungal mutant; glucan synthase; microbial activity; ultraviolet irradiation; wild relative; Trichoderma pseudokoningii; Trichoderma reesei